2021
DOI: 10.1038/s41598-021-91299-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Covid-19 confinement on the mental health of children and adolescents in Spain

Abstract: In Spain, in order to control COVID-19 transmission, one of the strictest confinement measures in the world for children and teenagers has been implemented. From 14 March to 26 April 2020 underage Spaniards were not allowed to leave their homes, except for reasons of force majeure. This could have consequences on their mental health in both the short and the long term. Thus, the aim of the present study was to explore the consequences of confinement on the mental health of Spanish children and teenagers, at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 40 publications
10
73
1
3
Order By: Relevance
“…It should be noted that the anxiety and depression symptoms were also exacerbated among young adolescents across this pandemic, this finding is in line with a growing body of literature that argues that the COVID-19 pandemic generally had adverse effects on youth mental health ( Meherali et al, 2021 ; Pizarro-Ruiz and Ordóñez-Camblor, 2021 ; Ran et al, 2020 ; Singh et al, 2020 ). Although the majority of epidemiological studies during the pandemic adopted a cross-sectional design, a few longitudinal studies emerged and provided support to our findings.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It should be noted that the anxiety and depression symptoms were also exacerbated among young adolescents across this pandemic, this finding is in line with a growing body of literature that argues that the COVID-19 pandemic generally had adverse effects on youth mental health ( Meherali et al, 2021 ; Pizarro-Ruiz and Ordóñez-Camblor, 2021 ; Ran et al, 2020 ; Singh et al, 2020 ). Although the majority of epidemiological studies during the pandemic adopted a cross-sectional design, a few longitudinal studies emerged and provided support to our findings.…”
Section: Discussionsupporting
confidence: 80%
“…However, children and adolescents are not a homogeneous population. It was found that children and teenagers were disproportionally impacted by confinement due to COVID-19, with children showing more rebellious behavior and teenagers presenting with more affective symptoms ( Pizarro-Ruiz and Ordóñez-Camblor, 2021 ). Zhou et al suggested that adolescents in higher grades exhibited more severe anxiety and depression symptoms ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One consequence of the COVID-19 pandemic and associated lockdowns and social distancing measures has been a decrease in adolescent self-esteem and an associated increase in depression ( Rossi et al, 2020 ; Pizarro-Ruiz and Ordonez-Camblor, 2021 ). In Spain, children and adolescents were not allowed to leave their homes except for emergencies from mid-March to late April 2020, and during this time, a survey was conducted to examine the impact of such confinement on young people’s wellbeing ( Pizarro-Ruiz and Ordonez-Camblor, 2021 ). One such outcome was a decrease in self-esteem, with girls showing lower self-esteem than boys ( Pizarro-Ruiz and Ordonez-Camblor, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Spain, children and adolescents were not allowed to leave their homes except for emergencies from mid-March to late April 2020, and during this time, a survey was conducted to examine the impact of such confinement on young people’s wellbeing ( Pizarro-Ruiz and Ordonez-Camblor, 2021 ). One such outcome was a decrease in self-esteem, with girls showing lower self-esteem than boys ( Pizarro-Ruiz and Ordonez-Camblor, 2021 ). Moreover, although no studies were found examining adolescents specifically since COVID-19, in line with the hypothesis that self-esteem serves as a buffer against negative mental health outcomes, results showed that self-esteem mediated the relationship between fear of COVID-19 and depression ( Rossi et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among Turkish senior high school students, exam anxiety was found to have a negative effect on sleep quality [12]. A group of Spanish adolescents found that the mental health of girls was more affected by COVID-19 confinement than boys, exhibiting more anxiety, less self-esteem, more problems with emotional regulation, and more physical dissatisfaction [13]. Depression, anxiety, and suicidal ideation were also reported more frequently among girls in studies of a sample of high school students from China and Jordan [9,14].…”
Section: Introductionmentioning
confidence: 99%